Photo-ID as a tool for studying and monitoring the endangered Saimaa ringed seal - Koivuniemi, M; Auttila, M; Niemi, M; Levänen, R; Kunnasranta, M (Endangered Species Research, 2016)
Photo-identification (photo-ID) with camera traps was examined as a non-invasive method for studying and monitoring the endangered Saimaa ringed seal Phoca hispida saimensis. An average of 51 game cameras were set up at shoreline haul-out sites in central Lake Saimaa during the moulting seasons in each of the years from 2010 to 2014. Individuals were identified from their lifelong unique lateral fur patterns. A total of 220000 digital images of seals were obtained from these game cameras and from digital cameras during this period, allowing 164 individuals to be identified, 43% of which were re-sighted in successive years. In the majority of game camera images, both sides of the seal were shown, and it was possible to determine the sex of the seal. The average distance between sightings of individual seals in different years was 1.6 km, suggesting that Saimaa ringed seals exhibit a high degree of moulting site fidelity. In addition, the results support suggestions of natal site fidelity. We propose that photo-ID sampling based on camera traps, and larger-scale photographic survey of the seals, should be implemented as a population monitoring tool of the Saimaa ringed seal. Further application of the photo-ID technique may facilitate mark-recapture population and survival rate estimates for this threatened seal species and provide significant insights into its life history and social behaviour.